Windows server 2008 bible - Shapiro, Jeffrey R. (Bible., 2008)
This version of the Windows server bible will be the largest yet, catering to what is certainly the most advanced operating system introduced by Microsoft. The book will cater to the needs of the server administration community and is designed to be a critical reference.